Field performance and genetic analysis of selected tomato (Lycopersicon esculentum Mill.) genotypes - Mitul, RY; Haque, MA; Rima, SA; Begum, SN (Journal of the Bangladesh Agricultural University, 2016)
The study was carried out in the field laboratory of the Department of Genetics and Plant Breeding of Bangladesh Agricultural University in order to evaluate varietal performance and genetic variability of fourteen tomato genotypes based on morphological and biochemical characteristics. Tomato genotypes were collected from Genetics and Plant Breeding farm, Bangladesh Agricultural University, Mymensingh. The field experiment was conducted from October 2014 to March 2015 with Randomized Complete Block Design (RCBD) including three replications. Data for genetic analyses were collected on seven traits viz. days to first flowering, pollen grain fertility, days to first fruit maturity, individual fruit weight, plant height, ascorbic acid content and yield per plant. ANOVA showed significant variation among the tomato genotypes for all the traits. Wide range existed between minimum and maximum mean values for all the genotypes whereas genotype World champion had the maximum individual fruit weight with the highest yield. On the other hand, genotype CI-170-0-20-2-0 gave poor performance. Yield exhibited a positive significant correlation with individual fruit weight; and in path coefficient analysis, maximum positive direct effects were found through individual fruit weight followed by plant height, ascorbic acid content and days to first fruit maturity. In principal component analysis, the main three components contributed approximately 79.14% of total variability. Genotypes were classified into five clusters by Wards method including late maturing and low yielder genotypes in cluster I, early flowering genotypes in cluster II, high yielder with large fruited genotypes in cluster III, genotypes containing low ascorbic acid in cluster IV and genotypes having early maturity with small fruit but minimum pollen grains fertility rate in cluster V. Based on the present findings, World champion and Big cherry were considered as superior varieties among the fourteen genotypes and individual fruit weight might be considered as an important criteria for yield improvement. J. Bangladesh Agril. Univ. 14(1): 31-36, June 2016